Passive transfer of narcolepsy: Anti-TRIB2 autoantibody positive patient IgG causes hypothalamic orexin neuron loss and sleep attacks in mice (2013)
Narcolepsy is a sleep disorder characterized by excessive daytime sleepiness and cataplexy (a sudden weakening of posture muscle tone usually triggered by emotion) caused by the loss of orexin neurons in the hypothalamus. Autoimmune mechanisms are implicated in narcolepsy by increased frequency of specific HLA alleles and the presence of specific autoantibody (anti-Tribbles homolog 2 (TRIB2) antibodies) in the sera of patients with narcolepsy. Presently, we passively transferred narcolepsy to naïve mice by injecting intra-cerebra-ventricularly (ICV) pooled IgG positive for anti-TRIB2 antibodies. Narcolepsy-IgG-injected mice had a loss of the NeuN (neuronal marker), synaptophysin (synaptic marker) and orexin-positive neurons in the lateral hypothalamus area in narcolepsy compared to control-IgG-injected mice and these changes were associated with narcolepsy-like immobility attacks at four weeks post injection and with hyperactivity and long term memory deficits in the staircase and novel object recognition tests. Similar behavioral and cognitive deficits are observed in narcoleptic patients. This is the first report of passive transfer of experimental narcolepsy to naïve mice induced by autoantibodies and supports the autoimmune pathogenesis in narcolepsy. © 2013 Elsevier Ltd.